Association between oral corticosteroid use and pyogenic liver abscesses in a case-control study - Lai, Shih-Wei (Biomedicine (Taipei), 2018)
Background and aim: There are no epidemiological studies focusing on the association between oral corticosteroid use and pyogenic liver abscesses. The aim of the study was to assess whether oral corticosteroid use is associated with increased odds of pyogenic liver abscesses in adults in Taiwan. Methods: This retrospective population-based case-control study was conducted to analyze the database of the Taiwan National Health Insurance Program from 2000 to 2013. Subjects aged 20 to 84 years with their first episode of pyogenic liver abscesses were assigned as the cases (n = 881). Randomly selected subjects without pyogenic liver abscesses aged 20 to 84 years were selected as the controls (n = 3207). A multivariable logistic regression model was used to assess the odds ratio and 95% confidence interval for the correlation of oral corticosteroid use with pyogenic liver abscesses. Results: After regulating for confounders, the adjusted odds ratio of pyogenic liver abscesses was 1.40 for subjects currently using oral corticosteroids (95% confidence interval 1.14, 1.70), compared with subjects who never used them. Upon further analysis, the adjusted odds ratio of pyogenic liver abscesses was 1.03 for subjects with current use of oral corticosteroids when increasing dosage for every one mg (95% CI 1.01, 1.06). Conclusion: Although the findings are not unexpected, they are important because they suggest that current use of oral corticosteroids is significantly associated with increased odds of developing pyogenic liver abscesses in adults in Taiwan, with a dose-dependent effect.